The Social Security of Farmers in Poland and in Selected EU Member States - Bak, Joanna; Szałkowska, Małgorzata (Olsztyn Economic Journal, 2020)
The subject of the present article is the social security of farmers. The main aim of this research paper is characterizing the functioning of the social security system for Polish farmers in comparison to such systems in selected member states of the European Union. The research investigated social security systems in Finland, France, Austria, Germany and Poland. The research involved a review of the literature on social security systems for farmers, provisions of law regulating the principles of such systems and the information furnished by the Agricultural Social Insurance Fund (KRUS), as well as statistical data provided by KRUS and Eurostat. The following research methods have been applied: descriptive analysis of the documents in order to verify the diversity of agricultural security systems, a critical review of the literature and online data concerning social security, and a comparative analysis. Each of the investigated countries has its own, distinct social and historical conditions, which has led to the development of independent institutions of social security for farmers. One factor which all these systems have in common is significant support from the national budget. In the future, financial inefficiency may pose the most significant risk to security systems in agriculture. Except for their social role, the social security systems presented below also participate in the management of agricultural policy, the aim of which is the development of rural areas and the welfare of the natural environment.